Impact of Farm Biogas Plant Auxiliary Equipment on Electrical Power Quality - Zbigniew Skibko; Andrzej Borusiewicz; Jacek Filipkowski; Łukasz Pisarek; Maciej Kuboń (Energies, 2025)
Devices that meet the needs of agricultural biogas plants represent a significant share of the energy balance of the source. The digester mixer is a crucial component installed in the fermentation chamber. Energy consumption during mixing depends on the regime and intensity, as well as the rheological properties of the carrier liquid, the dry matter content, and the dimensions of the fibers. Bioreactor operators often oversize mixers and extend mixing duration to avoid disruptions in biogas production. This paper analyzed the influence of digester mixer operations on selected electrical power quality parameters. For this purpose, two agricultural biogas plants with a capacity of 40 kW, connected to the low-voltage grid, were studied (one located approximately 120 m from the transformer station and the second 430 m away). As shown by the correlations presented in the article, the connection point of the biogas plant significantly impacted the magnitude of the influence of mixer operations on the analyzed voltage parameters. In the second biogas plant, switching on the mixers (in the absence of generation) caused the grid voltage to drop to the lower value permitted by regulations. (Switching on the mixers caused a change in voltage by about 30 V.) The most disturbances were introduced into the grid when the power generated by the biogas plant was equal to the power consumed by its internal equipment. (THDI then reached as high as 63.2%, while in other cases, it did not exceed 17%.) Furthermore, the operation of the mixers alone resulted in a reduction of approximately 1 MWh of energy exported to the power grid per month.